2012
DOI: 10.1038/pr.2012.72
|View full text |Cite
|
Sign up to set email alerts
|

High-field diffusion tensor imaging characterization of cerebral white matter injury in lipopolysaccharide-exposed fetal sheep

Abstract: Background:In gyrencephalic species such as sheep, precise anatomical and microstructural characterization of the consequences of fetal inflammation remains scarce. The goal of this study was to characterize changes in white matter (WM) structure using advanced magnetic resonance imaging (MRI) following lipopolysaccharide (LPS) exposure in the pretermequivalent fetal sheep. Methods: Preterm (0.7 gestation) fetal sheep received vehicle (Sham group) or LPS (LPS group), and fetal brains were collected 10 d later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
(64 reference statements)
2
20
0
Order By: Relevance
“…Recently, we observed reductions in both white matter volume (~21%) and cortical tissue (~18%) when brains were examined 10 days after LPS exposure in fetal sheep [149]. These neuropathological changes were also confirmed by ex vivo magnetic resonance imaging analysis [150]. Importantly, we found that there was loss of the normal maturational increase in cortical electroencephalography amplitude, which correlated with reduced cortical volumes.…”
Section: Role Of Tlrs In Perinatal Brain Damagesupporting
confidence: 72%
“…Recently, we observed reductions in both white matter volume (~21%) and cortical tissue (~18%) when brains were examined 10 days after LPS exposure in fetal sheep [149]. These neuropathological changes were also confirmed by ex vivo magnetic resonance imaging analysis [150]. Importantly, we found that there was loss of the normal maturational increase in cortical electroencephalography amplitude, which correlated with reduced cortical volumes.…”
Section: Role Of Tlrs In Perinatal Brain Damagesupporting
confidence: 72%
“…The LPS model was used to demonstrate the sensitivity of different PET ligands to neuroinflammation, further validated the use of histological markers that coincide with the PET signal (e.g., Dickens et al, 2014; Dobos et al, 2012; Liraz-Zaltsman et al, 2011). The LPS model has also been applied to other imaging modalities (e.g., Lodygensky et al, 2014; Moshkin et al, 2012; van de Looij et al, 2012), including a small number of human studies (e.g., Harrison et al, 2014; also see review in Schedlowski et al, 2014). Such models could also be used to validate other imaging modalities, although some critics argue that LPS induces much higher levels of microglial activations than are expected in neurodegenerative disorders (Streit et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is a powerful tool to probe cerebral white matter through a 3D description of water diffusion in the tissue [25]. Changes in diffusivity values (mean: MD, parallel: D // and orthogonal: D ⊥ ) and/or fractional anisotropy (FA) derived from DTI reveal loss of brain microstructure integrity [26], [27]. 1 H magnetic resonance spectroscopy ( 1 H-MRS) has been used to follow the changes in “neurochemical profile” of the brain during cerebral development [28].…”
Section: Introductionmentioning
confidence: 99%